2017
DOI: 10.15252/msb.20177554
|View full text |Cite|
|
Sign up to set email alerts
|

An immediate–late gene expression module decodes ERK signal duration

Abstract: The RAF‐MEK‐ERK signalling pathway controls fundamental, often opposing cellular processes such as proliferation and apoptosis. Signal duration has been identified to play a decisive role in these cell fate decisions. However, it remains unclear how the different early and late responding gene expression modules can discriminate short and long signals. We obtained both protein phosphorylation and gene expression time course data from HEK293 cells carrying an inducible construct of the proto‐oncogene RAF. By ma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 55 publications
(58 citation statements)
references
References 80 publications
1
57
0
Order By: Relevance
“…3b , fourth panel; Additional file 1 : Figure S3a). IER2 is induced by the MAP kinase pathway [ 28 ], which is in turn activated by the infection itself [ 29 ]. Similarly to IER2, the pro-apoptotic gene ING1 [ 30 ] was induced by MAP kinases as well, and, like IER2, showed higher mRNA levels at all timepoints after infection compared to uninfected cells under PAA treatment.…”
Section: Resultsmentioning
confidence: 99%
“…3b , fourth panel; Additional file 1 : Figure S3a). IER2 is induced by the MAP kinase pathway [ 28 ], which is in turn activated by the infection itself [ 29 ]. Similarly to IER2, the pro-apoptotic gene ING1 [ 30 ] was induced by MAP kinases as well, and, like IER2, showed higher mRNA levels at all timepoints after infection compared to uninfected cells under PAA treatment.…”
Section: Resultsmentioning
confidence: 99%
“…HEK293∆RAF1:ER cells were acquired and cultured as previously described 37 . Before treatments, cells were starved in serum-free medium overnight.…”
Section: Methodsmentioning
confidence: 99%
“…2C; Traverse et al, 1992), leading to the hypothesis that ERK dynamics could represent the activating ligand and receptor identity. Numerous subsequent studies in the same experimental system have revealed how pERK duration encoding and decoding arise both from the activity of the ligand-receptor complexes and downstream signal processing circuits (Kao et al, 2001;Marshall, 1995;Murphy et al, 2002Murphy et al, , 2004Santos et al, 2007;Sasagawa et al, 2005;Traverse et al, 1994;Uhlitz et al, 2017;Whitmarsh, 2007). Nevertheless, it has remained unclear to what extent transient and sustained ERK activity can explain the distinct cellular phenotypes, especially at the single cell level.…”
Section: Discriminating Rtk Ligandsmentioning
confidence: 99%